2013
DOI: 10.1080/10503307.2013.787497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of providing patient progress feedback and clinical support tools to psychotherapists in an inpatient eating disorders treatment program: A randomized controlled study

Abstract: Research on the effects of progress feedback and clinician problem-solving tools on patient outcome has been limited to a few clinical problems and settings (Shimokawa, Lambert, & Smart, 2010). Although these interventions work well in outpatient settings their effects so far have not been investigated with eating-disordered patients or in inpatient care. In this study, the effect of providing feedback interventions was investigated in a randomized clinical trial involving 133 females diagnosed with anorexia n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 51 publications
0
56
3
1
Order By: Relevance
“…Lambert et al (2003) and Shimokawa, Lambert, and Smart (2010) found much larger effects of feedback on outcome compared to no feedback, ranging between .28 and .70, but their meta-and mega-analyses included only studies from their own research group and were mainly conducted in the university counselling centre. More recent trials, both inside and outside Lambert's group, have shown more moderate but consistent effects of feedback (Bickman, Douglas Kelley, Breda, De Andrade, & Riemer, 2011;Byrne, Hooke, Newnham, & Page, 2012;Newnham, Hooke, & Page, 2010;Reese, Norsworthy, & Rowlands, 2009;Simon et al, 2013;Simon, Lambert, Harris, Busath, & Vazquez, 2012).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lambert et al (2003) and Shimokawa, Lambert, and Smart (2010) found much larger effects of feedback on outcome compared to no feedback, ranging between .28 and .70, but their meta-and mega-analyses included only studies from their own research group and were mainly conducted in the university counselling centre. More recent trials, both inside and outside Lambert's group, have shown more moderate but consistent effects of feedback (Bickman, Douglas Kelley, Breda, De Andrade, & Riemer, 2011;Byrne, Hooke, Newnham, & Page, 2012;Newnham, Hooke, & Page, 2010;Reese, Norsworthy, & Rowlands, 2009;Simon et al, 2013;Simon, Lambert, Harris, Busath, & Vazquez, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Feedback seems mainly effective for patients who are not doing well in therapy, the so called "not on track" (NOT) cases (Carlier et al, 2012;Lambert et al, 2003), although some studies have found feedback to be equally effective for both "on track" (OT) and NOT cases Simon et al, 2013). NOT cases are typically identified as being those individuals who fall out of range of a positive expected treatment response.…”
Section: Introductionmentioning
confidence: 98%
“…Simon et al [34] studied these methods with female eating disorder patients treated in an inpatient setting. These individuals had chronic courses and high levels of comorbidity.…”
Section: Broad Applicability Of Feedbackmentioning
confidence: 99%
“…Hasta este momento, las respuestas a las preguntas sobre la efectividad y la utilidad de esta elaborada herramienta de resolución de problemas permanece abierta. Sin embargo, en base a la literatura acumulada en este campo (por ej., Shimokawa et al, 2010;Simon et al, 2013), se puede suponer que el uso de la herramienta por parte de los clínicos tendrá un efecto positivo en el resultado del tratamiento para pacientes con riesgo, aunque pueden existir restricciones (p. ej., De Jong et al, 2017;Lutz et al, 2015).…”
Section: Discussionunclassified